Habitção de interesse social no meio rural : estudo de caso das vilas rurais da região metrpolitana de Maringá-PR - Moreira, Fábia Rosas (2014)
The paper presents study of a Rural Village of a Region Metropolitan Maringá - PR, seeking to assess the housing program and the architecture design of housing units according to the theme of worthy housing. The goal is to establish a set of recommendations that are the basis for future work dealing with programs and projects of social housing for the rural areas. The method used is the Post-Occupancy Evaluation that through assessment instruments Walkthrough, interviews, questionnaire and physical measurements made possible the organization of data measured on the spot in concrete results, along with examples of rural housing programs put in place in South America made it possible to propose recommendations for the revision of the Rural Villages program, as well as others with the same characteristics. The results identify problems, for example, in the execution and implementation of the program and also in architectural design implanted in allotment, but also shows progress. At the end, the research contributes to the theme of rural housing under the view of the architecture in order to subsidize new information future papers and public policies that address this subject